Anti-GD2 mAb and Vorinostat synergize in the treatment of neuroblastoma. (2nd June 2016) - Kroesen, Michiel; Büll, Christian; Gielen, Paul R.; Brok, Ingrid C.; Armandari, Inna; Wassink, Melissa; Looman, Maaike W. G.; Boon, Louis; den Brok, Martijn H.; Hoogerbrugge, Peter M.; Adema, Gosse J.
ABSTRACT: Neuroblastoma (NBL) is a childhood malignancy of the sympathetic nervous system. For high-risk NBL patients, the mortality rate is still over 50%, despite intensive multimodal treatment. Anti-GD2 monoclonal antibody (mAB) in combination with systemic cytokine immunotherapy has shown clinical efficacy in high-risk NBL patients. Targeted therapy using histone deacetylase inhibitors (HDACi) is currently being explored in cancer treatment and already shows promising results. Using our recently developed transplantable TH-MYCN NBL model, we here report that the HDAC inhibitor Vorinostat synergizes with anti-GD2 mAb therapy in reducing NBL tumor growth. Further mechanistic studies uncovered multiple mechanisms for the observed synergy, including Vorinostat-induced specific NBL cell death and upregulation of the tumor antigen GD2 on the cell surface of surviving NBL cells. Moreover, Vorinostat created a permissive tumor microenvironment (TME) for tumor-directed mAb therapy by increasing macrophage effector cells expressing high levels of Fc-receptors (FcR) and decreasing the number and function of myeloid-derived suppressor cells (MDSC). Collectively, these data imply further testing of other epigenetic modulators with immunotherapy and provide a strong basis for clinical testing of anti-GD2 plus Vorinostat combination therapy in NBL patients.